Custos de provisão de cestas de bens públicos - Duarte, Lucas Monteiro (2008)
For decades economists have been concerned with calculating the Marginal Cost of Public Funds (MCF). One of the greatest achievements in that area is the model of public good provision with distortionary taxation of Wildasin (1984). We have generalized Wildasin’s model to include a basket of public goods, allowing those goods to be in kind and cash transfer. Afterwards we make various estimates of the MCF in Brazil, including those that do not assume independence between the level of public good and the labor supply curve, which is standard in the literature. Our results show that the Marginal Cost of Public Funds in Brazil is relatively low. This low estimates are due, in part, to the small sensitivity of the labor supply curve to government expenditure estimated with Brazilian data.